Kebijakan Pemerintah Desa Guna Membangun Pariwisata Dalam Rangka Meningkatkan Pendapatan Ekonomi Masyarakat Di Desa Kuranji Dalang Kab. Lombok Barat - Nurmalasari Nurmalasari; Ilham Zitri; Yudhi Lestanata (Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze the policies of the Kuranji Dalang Village government in developing the tourism sector and to examine the extent to which these policies are able to integrate local potential with sustainable village development planning. This study uses a qualitative approach with a case study method. Data was obtained through in-depth interviews, observation, and documentation involving village officials, community leaders, and local residents. Data analysis was conducted through the stages of data reduction, data presentation, and interactive conclusion drawing. The results of the study show that Kuranji Dalang Village has considerable potential for marine tourism, particularly in the coastal area, which has a direct economic impact on the community through fishing and small businesses such as food and beverage sales. However, the village government does not yet have a specific vision and mission formally directed at tourism development, so existing policies are still general and unstructured. Tourism development is more focused on basic infrastructure development and the formation of community groups such as Pokdarwis and MSMEs, which indicates efforts towards a community-based tourism approach. The main obstacles faced include budget constraints, weak coordination, low community participation in village deliberations, and a lack of regulations related to visitor safety and supervision. Nevertheless, the level of community trust in the village government is relatively high, which is an important social capital in sustainable tourism development. This study concludes that tourism development in Kuranji Dalang Village requires strengthening more targeted village policies, increasing institutional capacity, and active community participation so that tourism can develop inclusively and sustainably in accordance with the principles of sustainable tourism.